Comparison of Incident of Chronic Pain Post Operations of Preperitoneal Transabdominal Herniorafi Laparoscopy (TAPP) and Totally Extraperitoneal (TEP) in General Hospital Dr. M. Djamil Padang - Ramata, Yudi Ichsan; M. Iqbal Rivai; Avit Suchitra (Biomedical Journal of Indonesia, 2021)
A B S T R A C TIntroduction : Inguinal herniation is a protrusion of peritoneal component throughabdominal wall caused by the weakness of aponeurotica tissue of abdomen. Inguinalherniation is the most common herniation cases in which 291.145 patient registeredin Indonesia at 2012 and 87 patients in General Government Hospital of M. DjamilPadang at 2017-2018. Herniation treatment is consisted of herniorrhapylaparoscopy using the TEP or TAPP techniques and both of them are related to theincidence of chronical post-operative pain that was defined by IASP as anuncomfortable sensation lasting for more than 3 months. Method: This researchwas using retrospective study design. The research was conducted at RSUP Dr. M.Djamil Padang in August – October 2020 with 54 samples. Result: The study foundthere was 54 cases of inguinal herniation fit to the inclusion criteria with peak ageof 82 years old and average of 59.1 years old. Most patients were male (79.62 %).There were 2 patients having chronic pain (7.41%) after herniorrhapy using the TAPPtechnique and 1 more (3.71%) having chronic pain with TEP technique. Bivariateanalysis was done by Fisher Exact Test and the study concluded there was nostatistical significance in relationship of chronic post-operative pain incidence withthe particular technique chosen at herniorrhapy laparoscopy (p=1.000). Conclusion:There was no significant relationship between the incidence of postoperative chronicpain in patients undergoing laparascopic hernioraphy and TEP or TAPP procedure.